2022
DOI: 10.1111/mbe.12312
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Gender Gaps in Mathematics Achievement: Elevated Stakes during Performance as One Explanation

Abstract: Gender gaps in mathematics achievement persist in many contexts and when visible, these gaps are paradoxical. Low-stakes measures of mathematics achievement such as grades and study behaviors favor girls, while gaps tend to reverse on assessments/competitions. We explore whether different impacts of raising performance stakes could be one explanation. Study 1 experimentally manipulated the stakes by imposing a performance-contingent, social-evaluative pressure either: before instruction (n = 66), before testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The meta-analysis by Voyer and Voyer (2014) does find an overall female advantage in scholastic achievement in mathematics. In line with this result, Lyons et al (2022) concluded that low-stakes measures of mathematics achievement, such as grades, favor female students, while high-stakes measures (such as the admission test) tend to reverse the gap. As Gallagher and Kaufman (2005) pointed out, females regularly get lower scores than males when considering standardized tests of mathematics, although no differences exist in the classroom.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The meta-analysis by Voyer and Voyer (2014) does find an overall female advantage in scholastic achievement in mathematics. In line with this result, Lyons et al (2022) concluded that low-stakes measures of mathematics achievement, such as grades, favor female students, while high-stakes measures (such as the admission test) tend to reverse the gap. As Gallagher and Kaufman (2005) pointed out, females regularly get lower scores than males when considering standardized tests of mathematics, although no differences exist in the classroom.…”
Section: Introductionmentioning
confidence: 69%
“…Griselda (2020) concluded that males perform better than females in tests where there is a higher proportion of multiple-choice questions (as the test used in university admission process analyzed in this paper), but when grades are used they frequently favor girls. Similarly, Lyons et al (2022) stated that low-stakes measures of mathematics achievement (such as grades), favor female students, while high-stakes measures (such as the admission test) tend to reverse the gap. Therefore, our results are fully consistent with previous research, and suggest that the gap detected at entry is a consequence of using standardized tests.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Soysal et al (2022) indicate that the level of students' confidence is the main factor to predict their mathematics anxiety. There have been numerous studies revealing gaps in mathematics performance among students (Brezavšček et al, 2020;Dossi et al, 2021;Le et al, 2023;Lyons et al, 2022;Tolley et al, 2012), but few have investigated students' motivation for mathematical success. Therefore, this research study adds to the body of the relevant academic literature by producing and integrating three mathematical models, which are developed to optimize students' motivation for mathematical success.…”
Section: Introductionmentioning
confidence: 99%